Implementation of the M.O.I.S.T. concept for the local treatment of chronic wounds into clinical practice. Issue 4 (2022) - Dissemond, Joachim; Malone, Matthew; Ryan, Hayley; Tanaka, Rica; Ohura, Norihiko; Wong, Keng Lin; AiLing, Hu; Long, Zhang; Yoon, Kim Jung; Angspatt, Apichai; Nair, Harikrishna K.R.
No abstract available